The heart of the matter (high performance athletes` perceptions of the coach-athlete relationship) - Infurna, C. (Techniques Magazine, 2023)
Relationships between coaches and athletes play a critical role in the athlete´s overall sport performance (Phillipe & Seiler, 2006), and has increasingly been the subject of empirical research (Jowett & Cockerill, 2003; Infurna, 2022). A large number of studies have examined the coach-athlete dyad across professional (Gearity & Murray, 2011; Staff et al., 2017) and Olympic (Jowett & Cockerill, 2003) settings. More recently, research has also focused on coach-athlete relationships in collegiate settings (Simons & Bird, 2022; Criticos, Layne, Simonton, & Irwin, 2020) and post competitive experiences (Harry & Weight, 2021). Prior research that focused on elite athletes has reported that talent development is dependent upon quality coaching (Cote, Baker, & Abernethy, 2003; Jowett & Cockerill, 2003; Infurna, 2022). There are many factors that contribute to the success of the coach-athlete dyad, such as: open communication, establishing trust and rapport, trustworthiness, coach autonomy, supportive behaviors and building credibility (Mageau & Vallerand, 2003; Deci & Ryan, 2000; Infurna, 2022). Previous researchers have suggested that an effective and mutually beneficial coach-athlete relationship plays a vital role in the athelete´s success, and that that coaches are an important source of support for their athletes (Harry & Weight, 2021). A current gap in the empirical literatur exists between different types of coach-athlete dyads at various levels. Minimal empirical literature has been devoted to collegiate dyads (Simons & Bird, 2022; Criticos et al., 2020; Vella et al., 2013), therefore the purpose of this retrospective study is to further understand the dynamic relationshios between elite collegiate athletes and their coaches. The following research question was proposed to guide this study: What can we learn about elite post-collegiat athlete perceptions of their relationship with their collegiat throwing coaches?